Contractors’ Environmental Sustainability: The Roles of Innovativeness and Market Orientation - Jibril Adewale Bamgbade; Kamaruddeen Ahmed Mohammed; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2016)
This paper aims to conceptualise the influence of certain organisational innovativeness factors and market orientation on environmental sustainability adoption by Malaysian large contractors. The framework developed in this study intends to establish the link between product innovativeness, process innovativeness, and market orientation (as predictors) and environmental sustainability (the criterion variable) using organisational readiness for change theory to underpin these relationships. Although, it is expected that the findings of this study can be used to develop strategies that could improve environmental sustainability adoption among these contractors, this study did not consider other factors that could also explain the environmental sustainability adoption. It is expected that this studys findings could assist in developing strategies to increase the rate of environmental sustainability adoption among the contractors. Again, it could also be useful for policy makers and other construction industry players.